Synthesis of highly luminescent mercaptosuccinic acid‐coated CdSe nanocrystals under atmospheric conditions. (18th March 2014) - Dong, Meiting; Xu, Jingyi; Liu, Shuxian; Zhou, Ying; Huang, Chaobiao
ABSTRACT Here we report a facile one‐pot method for the preparation of high‐quality CdSe nanocrystals (NCs) in aqueous solution under an air atmosphere. Compared with the traditional use of NaHSe or H2Se, the more stable sodium selenite is utilized as the Se source for preparing highly luminescent CdSe nanocrystals. By using mercaptosuccinic acid (MSA) as the capping agent and borate–citrate acid as the buffering solution, CdSe nanocrystals with high quantum yield (up to 70%) have been synthesized conveniently. The influence of different experimental parameters, such as the pH of the precursor solution, the molar ratio of Cd2+ to Na2SeO3 and Cd2+ to MSA on the CdSe nanocrystals, has been systematically investigated. The prepared CdSe NCs were spherical with a size of ~ 5 nm. Copyright © 2014 John Wiley & Sons, Ltd.